Organization health climate role on work engagement and promotive behavior - Xianran Huang (2023)
As the professional world becomes more globalized, it’s imperative for organizations to stay abreast of changes, and innovate to ensure they remain efficient and relevant. In this dynamic setting, cultivating a culture where employees speak up and remain invested is crucial. Voice, which is when employees share their thoughts, worries, or proposals, combined with engagement, where workers are deeply connected and devoted to their tasks, are pivotal in fostering organizational flexibility and creativity. By championing these elements, companies can more effectively tap into the collective wisdom and adaptability required to tackle the complex challenges and prospects of today’s business landscape. Studies have indicated that job resources are positively related with work engagement and promotive voice. In addition, work engagement plays a mediating role between job resources and promotive voice. This research explored the relation between three job resources - health climate, supervisor support, and coworker support - and their impact on work engagement as well as promotive voice. Afterwards, it tested the mediating role of work engagement between job resources and promotive voice. To do that, a quantitative study was conducted (N = 371) with employees work in a Portuguese multinational company. All the three hypotheses were partial confirmed by this research. Hypothesis 1 was partially confirmed; aside from coworker support, the other two job resources are positively related to work engagement. Hypothesis 2 was also partially confirmed; only supervisor support is positively related to promotive voice. Regarding Hypothesis 3, work engagement significantly partially mediates the relationships, indicating that an increase in health climate and coworker support is related to an increase in work engagement, which, in turn, is positively related to promotive voice.